2020
DOI: 10.1126/science.aay5958
|View full text |Cite
|
Sign up to set email alerts
|

Global ecosystem thresholds driven by aridity

Abstract: Aridity, which is increasing worldwide because of climate change, affects the structure and functioning of dryland ecosystems. Whether aridification leads to gradual (versus abrupt) and systemic (versus specific) ecosystem changes is largely unknown. We investigated how 20 structural and functional ecosystem attributes respond to aridity in global drylands. Aridification led to systemic and abrupt changes in multiple ecosystem attributes. These changes occurred sequentially in three phases characterized by abr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
568
1
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 696 publications
(602 citation statements)
references
References 109 publications
22
568
1
11
Order By: Relevance
“…3). Those findings have been reported in several ecosystems, globally [10] and regionally [132], and attain nitrogen cycling rates [22,132], micronutrients [79], soil fauna [24,135], changes in the relative importance of erosive agents [95], soil aggregates stability and the relationship between soils and plants [11]. Presumably, those changes would involve also a drastic change in soil microorganisms, which are the main biotic agents driving and connecting soil nutrients and stocks [23] and contribute importantly to enhance soil stability and water capacity.…”
Section: Terraforming Drylands: Synthetic Soilsmentioning
confidence: 55%
See 1 more Smart Citation
“…3). Those findings have been reported in several ecosystems, globally [10] and regionally [132], and attain nitrogen cycling rates [22,132], micronutrients [79], soil fauna [24,135], changes in the relative importance of erosive agents [95], soil aggregates stability and the relationship between soils and plants [11]. Presumably, those changes would involve also a drastic change in soil microorganisms, which are the main biotic agents driving and connecting soil nutrients and stocks [23] and contribute importantly to enhance soil stability and water capacity.…”
Section: Terraforming Drylands: Synthetic Soilsmentioning
confidence: 55%
“…Because tipping points deeply modify the concept of risk (there is no linear decay response as some external variables change) a different approach is needed to deal with their nature. Finally, also at the ecosystem level, different studies conducted in the field suggest the incidence of abrupt transitions in the soil system along spatial gradients of increasing aridity [11]. In particular, at certain aridity levels, corresponding to the inter-fase between semiarid and arid ecosystems, some studies have reported an abrupt transition of soil functioning (soil Preprints (www.preprints.org) | NOT PEER-REVIEWED | Posted: 29 December 2019 doi:10.20944/preprints201912.0383.v1…”
Section: Terraforming Drylands: Synthetic Soilsmentioning
confidence: 99%
“…Because tipping points deeply modify the concept of risk (there is no linear decay response as some external variables change) a different approach is needed to deal with their nature. Finally, also at the ecosystem level, different studies conducted in the field suggest the incidence of abrupt transitions in the soil system along spatial gradients of increasing aridity [117]. In particular, at certain aridity levels, corresponding to the inter-fase between semiarid and arid ecosystems, some studies have reported an abrupt transition of soil functioning (soil fertility and nutrient turnover rates) which correspond to patterns that fit in a catastrophic shift behavior [118] (see Figure 3).…”
Section: Terraforming Drylands: Synthetic Soilsmentioning
confidence: 97%
“…Bistability: dynamical system with two stable equilibria. Classic ecological examples are shallow and eutrophic lakes [62,63], vegetated or desert states in semiarid ecosystems [28,30] (see also [64]). Globally asymptotically stable equilibrium point: equilibrium point that is stable and such that all orbits of the system converge to it.…”
Section: Glossarymentioning
confidence: 99%
“…Moreover, external pressures like grazing or deforestation have shown that for the same aridity levels two possibilities are possible, vegetated or desert [28,29]. In lower levels of aridity multiple ecosystems can be observed (savanna, forest, grasslands, and shrublands) but for some levels of aridity abrupt changes occur [30]. Furthermore, in the framework of systems biology, a tipping point driving populations to extinction has been recently described experimentally in yeast [31].…”
Section: Introductionmentioning
confidence: 99%